Enlightenment Orientalism in the American mind, 1770-1807 - Pangborn, Matthew H. (Routledge, 2019)
"This study engages with the emerging field of energy humanities to provide close readings of several early American oriental-observer tales. The popular genre of orientalism offered Americans a means to critique new ideas of identity, history, and nationality accompanying protoindustrialization and a growing consumerism. The tales thus express a complex self-reflection during a time when America's exploitation of its energy resources and its engagement in a Franco-British world-system was transforming the daily life of its citizens. The genre of the oriental observer, this study argues, offers intriguing glimpses of a nation becoming strange in the eyes of its own inhabitants"-- Provided by the publisher.
Keywords: Orientalism -- United States -- History -- 18th century.; Orientalism -- United States -- History -- 19th century.; Energy consumption -- United States -- History.; Middle East -- Foreign public opinion, American.; Asia -- Foreign public opinion, American.; Orientalisme -- États-Unis -- Histoire -- 18e siècle.; Orientalisme -- États-Unis -- Histoire -- 19e siècle.; Énergie -- Consommation -- États-Unis -- Histoire.; SOCIAL SCIENCE -- General.; Energy consumption; Orientalism; Public opinion, American; Asia; Middle East; United States; 1700-1899; History